Coordinated posttranscriptional mRNA population dynamics during T‐cell activation - Neelanjan Mukherjee; Patrick J Lager; Matthew B Friedersdorf; Marshall A Thompson; Jack D Keene (Molecular Systems Biology, 2009)
Abstract Although RNA‐binding proteins (RBPs) coordinate many key decisions during cell growth and differentiation, the dynamics of RNA–RBP interactions have not been extensively studied on a global basis. We immunoprecipitated endogenous ribonucleoprotein complexes containing HuR and PABP throughout a T‐cell activation time course and identified the associated mRNA populations using microarrays. We used Gaussian mixture modeling as a discriminative model, treating RBP association as a discrete variable (target or not target), and as a generative model, treating RBP‐association as a continuous variable (probability of association). We report that HuR interacts with different populations of mRNAs during T‐cell activation. These populations encode functionally related proteins that are members of the Wnt pathway and proteins mediating T‐cell receptor signaling pathways. Moreover, the mRNA targets of HuR were found to overlap with the targets of other posttranscriptional regulatory factors, indicating combinatorial interdependence of posttranscriptional regulatory networks and modules after activation. Applying HuR mRNA dynamics as a quantitative phenotype in the drug‐gene‐phenotype Connectivity Map, we identified candidate small molecule effectors of HuR and T‐cell activation. We show that one of these candidates, resveratrol, exerts T‐cell activation‐dependent posttranscriptional effects that are rescued by HuR. Thus, we describe a strategy to systematically link an RBP and condition‐specific posttranscriptional effects to small molecule drugs.